Unraveling the Dynamics of Indole Acetic Acid-Producing Endophytic Bacteria: Insights into Plant Growth and Sustainable Agriculture - Gelfara Abednego; Christabel Haurisa (Journal Basic Science and Technology, 2023)
This research delves into the intricate world of plant-microbe interactions, focusing on the role of endophytic bacteria capable of producing Indole Acetic Acid (IAA). The investigation unfolds as a multidimensional exploration, encompassing the mechanisms, variability, and practical applications of IAA-producing endophytic bacteria for sustainable agriculture and environmental resilience. The study unveils the remarkable variability among different bacterial strains in their synthesis of IAA. Statistical analyses underscore significant differences, highlighting the individualistic nature of each strain and emphasizing the diversity encoded within the microbial ensemble. Strain-specific trends, temporal dynamics, and environmental responsiveness enrich our understanding of the nuanced contributions of these bacteria to plant growth. Mechanistically, IAA emerges as a key growth regulator influencing root morphogenesis, nutrient uptake, and stress tolerance. The research demonstrates how IAA-producing endophytic bacteria foster improved water use efficiency, nutrient mobilization, and disease resistance, presenting a holistic picture of their multifaceted role in shaping the resilience and productivity of plants. The development of bio-stimulants derived from robust IAA producers promises enhanced crop yields, reduced reliance on synthetic growth-promoting agents, and improved nutrient use efficiency. Mitigation of abiotic stress, promotion of symbiotic relationships, and contributions to biocontrol underscore the potential of IAA-producing endophytic bacteria in fostering sustainable agricultural practices.